The next SABV—stress as a biological variable - Bailey, Aleah; Jaspers, Ilona (Frontiers in Environmental Health, 2025)
The 2015 policy to incorporate sex as a biological variable (SABV) enhanced biomedical research and allowed for better predictions to be made regarding clinical outcomes and environmental health risks. This review aims to make a case for the next SABV—stress as a biological variable. While the body is equipped to respond to acute stress, chronic stress can overwork physiologic systems, leading to allostatic load, or progressive wear and tear on the brain and body. Allostatic load has many implications on immune, cardiovascular, and metabolic function, and alters xenobiotic metabolism of environmental and pharmaceutical chemicals. However, historically disadvantaged communities and populations are at an increased risk of harm due to elevated exposure to psychosocial stressors and environmental pollutants. Therefore, the unique biological responses among populations that experience this double hit should be considered in toxicology risk assessments. Among current approaches, allostatic load measurements are optimal as a framework that captures health disparities and a tool that quantifies cumulative stress burdens that can be integrated into health data for better risk predictions.